ANALISIS DAMPAK PEMEKARAN WILAYAH TERHADAP PENDAPATAN PER KAPITA, KEMISKINAN DAN KETIMPANGAN ANTARWILAYAH DI PROVINSI PAPUA - Ida Ayu Purba Riani; M. Pudjihardjo Pudjihardjo (Environmental Research Center (PPLH) of Udayana University, 2012)
The study is aimed at describing and analyzing the impact of regional extension on the economical aspect of Papua Province based on the indicators of public welfare such as per capita income, poverty, and interregional gap. By separating two time periods between before and after extension, and using average differential test, or t-test equal mean, it is estimated that regional extension policy significantly does not bring the per capita income to higher rate than before extension. In other word, statistically, there is no difference between per capita income between before and after extension. It is said that regional extension does not influence the per capita income. The strong significant indication shows that regional extension affects the decreased rate of urban poverty. It is, however, failed to reduce the rural poverty. In general, regional extension has significant effect on the reduction of poverty in Papua Province. Finally, regional extension policy is not statistically stronger, or less significant, to influence the interregional development gap in Papua Province. Based on the statistic result, it is generalized that regional extension policy in Papua Province has significant effect on the poverty reduction in Papua Province.